2020
DOI: 10.1155/2020/8306903
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll-Like Receptor 4 Gene Polymorphisms with Acute Aortic Dissection in a Chinese Han Population

Abstract: Background. Inflammation may be involved in the pathogenesis of acute aortic dissection (AAD). Toll-like receptor 4 (TLR4) is known to play a critical role in regulating the immune and inflammatory processes. To date, the relationship between genetic variation of TLR4 and AAD is far from clear. The purpose of our study was to illustrate the relevance of TLR4 polymorphisms with the susceptibility to AAD. Methods. A total of 222 AAD patients and 222 controls were enrolled in this study. Frequency distributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Previous experiments showed that inflammation could take part in structural damage of the aortic wall and the pathophysiological development of acute aortic dissection [9][10][11][12][13]. Lymphocyte-monocyte ratio (LMR) is a novel inflammatory biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments showed that inflammation could take part in structural damage of the aortic wall and the pathophysiological development of acute aortic dissection [9][10][11][12][13]. Lymphocyte-monocyte ratio (LMR) is a novel inflammatory biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Animal experiments and cell experiments showed that in ammation could take part in structural damage of the aortic wall and the pathophysiological development of acute aortic dissection [9][10][11][12][13]. Lymphocytemonocyte ratio (LMR) is a novel in ammatory biomarker.…”
Section: Introductionmentioning
confidence: 99%